2010
DOI: 10.5004/dwt.2010.1228
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of shells of hazelnut modified with Reactive Orange 122 as adsorbent for the removal of Cu(II)

Abstract: ab s t r ac tThe influence of reactive dye modification on the efficiency of adsorption capacities of hazelnut shells was investigated. To that end, natural adsorbents such as shells of unmodified hazelnut (RH), and modified hazelnut (MH) were used. The removal of Cu(II) by these adsorbents from aqueous solution was investigated by using several parameters such as modification, contact time, temperature and pH. The adsorption process attained equilibrium within 60 min. The extent of Cu(II) removal increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…As also seen in Table 3, the maximum adsorption of RW and MW for Cu(II) varied between 8.51 and 13.61; 15.22 and 17.42 mg g −1 , respectively. Previously, some researchers have investigated several adsorbents such as diatomite and modifi ed diatomite [17], fl y ash [10], sawdust [3], Pleurotus pulmonarius [16], peat [27], tea-industry waste [28], Rubber leaf powder [30], Rubber wood sawdust [31], Hazelnut husk A.C. [32], Carboxymethylated Chitosan Hydrogel Beads [33], chitosan hydrogel beads [34] and the shells of hazelnut modifi ed with Reactive Orange [40] for the removal of Cu(II). By comparison of the results obtained in this study with those in the prviously reported works (Table 4) on adsorption capacities of various low-cost adsorbent in aqueous solution for Cu(II), it can be stated that our fi ndings are good.…”
Section: First-order Kinetic Modelmentioning
confidence: 99%
“…As also seen in Table 3, the maximum adsorption of RW and MW for Cu(II) varied between 8.51 and 13.61; 15.22 and 17.42 mg g −1 , respectively. Previously, some researchers have investigated several adsorbents such as diatomite and modifi ed diatomite [17], fl y ash [10], sawdust [3], Pleurotus pulmonarius [16], peat [27], tea-industry waste [28], Rubber leaf powder [30], Rubber wood sawdust [31], Hazelnut husk A.C. [32], Carboxymethylated Chitosan Hydrogel Beads [33], chitosan hydrogel beads [34] and the shells of hazelnut modifi ed with Reactive Orange [40] for the removal of Cu(II). By comparison of the results obtained in this study with those in the prviously reported works (Table 4) on adsorption capacities of various low-cost adsorbent in aqueous solution for Cu(II), it can be stated that our fi ndings are good.…”
Section: First-order Kinetic Modelmentioning
confidence: 99%